RADIATION AND CADMIUM INDUCED TESTICULAR INJURY AND ITS AMELIORATION BY ALOE VERA EXTRACT - PUROHIT RK; BHATI SL; PURKHARAM; ISRAN R; AGARWAL M; CHAKRAWARTI A (International Journal of Pharma and Bio Sciences, 2015)
Extract of Aloe vera leaves has been used for treatment of various diseases and disorders in ayurveda and unani medicine. Modulatory effect of Aloe vera against radiation and cadmium induced changes in terms of histological alterations in testis has been studied in present investigation. For this purpose mouse exposed to 7.0 Gy radiation showed radiation induced sickness, including marked changes in histology of testis. The Aloe vera leaf extract was given orally at a dose of 1000 mg/kg body wt/animal/day for five consecutive days prior to irradiation. The radiation dose reduction factor was 1.65. Aloe vera pre treatment significantly prevents radiation and cadmium induced histopathological changes in cells. The study suggested that Aloe vera extract has exerted significant radioprotective effects on testis. It is well known that Aloe is an essential component of antioxidant defense system with participation at multiple cellular levels. Aloe has a protective effect on histological damage by maintaining membrane integrity due to its direct action of free radicals. It can be concluded that Aloe has a protective role against cytotoxicity induced by radiation and cadmium in the testes of Swiss albino mice.